Anti-N-Methyl-D-Aspartate Encephalitis as Paraneoplastic Manifestation of Germ-Cells Tumours: A Cases Report and Literature Review - Claudia Geraldine Rita; Israel Nieto Gañan; Adriano Jimenez Escrig; Ángela Carrasco Sayalero (Case Reports in Immunology)
Anti-N-methyl-D-aspartate (NMDA) receptor encephalitis is the most common form of autoimmune encephalitis, caused by the interaction between an antibody and its target, located on glutamate receptor type N-methyl-D-aspartate (NMDA) of neuronal surface. There is a wide spectrum of clinical features starting by a viral-like prodrome, followed by symptoms such as psychosis, aggressive behaviour, memory loss, seizures, movement disorders, and autonomic instability. Up to 50% of the affected young female patients have germ-cells tumours as ovarian teratoma, making it essential to establish an early diagnosis through detection of specific antibodies in serum and cerebrospinal fluid (CSF). This retrospective observational study was performed in patients whom positive anti-NMDA receptor antibodies have been tested, associated with clinical manifestations that suggest autoimmune encephalitis and a germ-cell tumour confirmed by pathology. Six patients have tested positive for anti-NMDA receptor antibodies associated with a germ-cell tumour and clinical manifestations of autoimmune encephalitis. Management includes aggressive immunosuppression and surgical removal.